Типология психопатогенетических механизмов формирования аффективных нарушений у пациентов, страдающих аддиктивной патологией = Typology of psychopathogenetic mechanisms of forming of affective disorders in patients suffering from addictive pathology - Grigoryan, A. Z. (Journal of Education, Health and Sport, 2015)
Grigoryan A. Z. Типология психопатогенетических механизмов формирования аффективных нарушений у пациентов, страдающих аддиктивной патологией = Typology of psychopathogenetic mechanisms of forming of affective disorders in patients suffering from addictive pathology. Journal of Education, Health and Sport. 2015;5(9):183-190. ISSN 2391-8306. DOI10.5281/zenodo.30526 http://dx.doi.org/10.5281/zenodo.30526 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A183-190 https://pbn.nauka.gov.pl/works/619781 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 29.08.2015. ТИПОЛОГИЯ ПСИХОПАТОГЕНЕТИЧЕСКИХ МЕХАНИЗМОВ ФОРМИРОВАНИЯ АФФЕКТИВНЫХ НАРУШЕНИЙ У ПАЦИЕНТОВ, СТРАДАЮЩИХ АДДИКТИВНОЙ ПАТОЛОГИЕЙ TYPOLOGY OF PSYCHOPATHOGENETIC MECHANISMS OF FORMING OF AFFECTIVE DISORDERS IN PATIENTS SUFFERING FROM ADDICTIVE PATHOLOGY А. З. Григорян A. Z. Grigoryan Коммунальное лечебно-профилактическое учреждение «Областной наркологический диспансер», г. Запорожье The municipal health care facility "Regional Drug Dispensary", Zaporozhye Abstract In order to form a typology of psychopathogenetic mechanisms of forming of affective disorders in structure of addictive pathology 100 patients "Zaporozhye Regional Narcologic Dispensary" suffering from affective disorders in the structure of, were examined. Using clinically-psychopathological method integrative systematic of etiopathogenetic mechanisms of affective disorders formation in the structure of addictive pathology, was developed. This mechanisms includes: pathoaffective, somatogenically-organic, patopersonologic, sociogenic, abstinent, intoxicative, emotional and of deprivation. Typical structural and dynamic versions of depressive and manioform syndromes was described. Keywords: polydrug use, psychopathogenesis, affective disorders, depression, manioform syndrome. Реферат С целью разработки типологии психопатогенетических механизмов формирования аффективных нарушений в структуре аддиктивной патологии было обследовано 100 пациентов КУ «Запорожский областной наркологический диспансер» ЗОР, страдающих аффективными расстройствами в структуре полинаркоманий. При использовании клинико-психопатологического метода была сформирована интегративная систематика этиопатогенетических механизмов формирования аффективных нарушений в структуре аддиктивной патологии, куда вошли следующие механизмы: патоаффективный, соматогенно-органический, патоперсонологический, социогенный, абстинентный, интоксикационный, эмоционально-депривационный. Описаны типичные структурно-динамические варианты депрессивных и маниоформных синдромов. Ключевые слова: полинаркомания, психопатогенез, аффективные нарушения, депрессия, маниоформный синдром.